Suspension of Detention for Children Acting in Self-Defense as a Form of Special Protection in the Juvenile Justice System - Siagian, Nurul Inayah; Aprilianda, Nurini; Istiqomah, Milda (International Journal of Business, Law, and Education, 2025)
Detention of children in the context of self-defense (noodweer) remains unregulated explicitly in Indonesia’s juvenile criminal justice system. Although Article 49 of the Indonesian Penal Code (KUHP) recognizes self-defense as a justifying or excusing ground, children may still be subjected to detention under general procedural provisions in the Criminal Procedure Code (KUHAP). This creates legal uncertainty and increases the risk of disproportionate treatment. This study employs a normative juridical method with a comparative approach, analyzing the German legal system, which limits juvenile detention and emphasizes psychological, educational, and proportionality considerations. The findings show an urgent need for Indonesia to formulate specific legal norms on the suspension of detention for children who commit acts of self-defense. Such reform is crucial to uphold children’s rights, prevent criminalization, and support restorative justice principles and humane treatment in the juvenile justice process.